Germinação de sementes de pessegueiro nas condições climáticas de Viçosa, Minas Gerais - Luiz Agnes, Ernani; Fortes, José Maurício; Cardoso, Antônio Américo; Dias Casali, Vicente Wagner; Teixeira Coelho, Dirceu (Revista Ceres, 2025)
The purpose of this research was to determine if peach seeds must be submitted to stratification in order to germinate properly, i.e., without producing dwarf seedlings or plants with abnormal leaf development, under the climatic con- ditions of Vigosa, Minas Gerais State, Brazil. S